PENGARUH KUALITAS PELAYANAN POOL SERVICE TEAM TERHADAP TINGKAT KEPUASAN TAMU DI VIBE DEPARTMENT HARD ROCK HOTEL BALI - Diyah Putri Anggraini (STIE BIITM, 2019)
Many things will be done by the hotel management to be able to attract tourists to choose to stay in their hotel. Starting from the facilities that have been provided by the hotel, the best quality of service, the appropriate prices and so forth, this is so that the guests staying can feel the satisfaction of the quality of services and products provided. This research aimed to analyze the influence of Service Quality of Pool Service Team On Guest Satisfaction at Vibe Department Hard Rock Hotel Bali. The sample of this research is 100 guests at Hard Rock Hotel Bali. The Data sources used in this research are primary and secondary data. Data is analyzed using path analysis that is assisted with SPSS for Windows version 22. Data collection method in this research using interview method, by means of questionnaires with likert scale. The analytical technique used is simple linier regression analysis. Results of statistical analysis known that the service quality of pool service team influenced on guest satisfaction is 26,2%, based on hypothesis testing with t-test results, it can be concluded that the service quality variable (X) partially and significantly positive influenced on guest satisfaction variable (Y) with value of t-test is 5,900 and sig. 0,000 at Vibe Department Hard Rock Hotel Bali.